Peningkatan Hasil Belajar KPK dan FPB dengan Pendekatan Contextual Teaching and Learning di Sekolah Dasar - Dewi, Nurmala; Masniladevi, Masniladevi; F, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was to describe the improvement KPK and FPB learning outcomes with the Contextual Teaching and Learning approach in class V SDN 06 Piai Tangah. This type of research is classroom action research, with a qualitative and quantitative approach. The subject of research were teachers and fifth grade students of SDN 06 Piai Tangah. The results obtained in the form of the average cycle I to cycle II are as follows: (1) RPP 82.14% (B) to 92.85% (SB) with an increase of 10.71%, (2) Implementation of learning based on: (a) teacher activity 78.57% (B) to 91.06% (SB) with an increase of 12.49%, (b) student activity 73.21% (C) to 91.06% (SB) with an increase of 17 , 85%, while (3) student learning outcomes (3 domain) 71.48%  (C) to 84.09%  (B) with an increase of 12.61%. It can be concluded that the Contextual Teaching and Learning approach can improve the learning outcomes of KPK and FPB in class V SDN 06 Piai Tangah. Keywords: learning outcomes, KPK and FPB, CTL approach